Development of technology for juice purification using dietary fiber, bentonite and filtroperlit - V. A. Loseva (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2013)
The pilot study examined the impact of combined sorbents on the effectiveness of juice purification, the extent of proteins removal and the degree of microbiological contamination of preliming juice.